ChemInform Abstract: Orthorombic HP‐REOF (RE: Pr, Nd, Sm — Gd) — High‐Pressure Syntheses and Single‐Crystal Structures (RE: Nd, Sm, Eu). Issue 51 (5th December 2016) - Glaetzle, Matthias; Schauperl, Michael; Hejny, Clivia; Tribus, Martina; Liedl, Klaus R.; Huppertz, Hubert
Abstract: High‐pressure polymorphs of LnOF (Ln: Pr, Nd, Sm, Eu, Gd) are prepared by hot press sintering of stoichiometric amounts of Ln2 O3 (or Pr6 O11 ) and LnF3 (multianvil press, 11 GPa, 1200 °C, 5 h).